AB0161 Interleukin-37: a therapeutic for lupus nephritis in mrl-faslpr mice. (12th June 2018) - Ding, L.; Hong, X.; Huang, Z.; Liu, D.
Abstract : Background: Systemic lupus erythematosus (SLE) is a serious and noticed autoimmune disease, and lupus nephritis (LN) as one of its major complications without effective treatment. IL-37 has been identified as a natural inhibitor of innate immunity. Although increasing evidence shown that serum IL-37 correlated with SLEDAI and nephritis activity, However, it is still unclear that the therapeutic effect of IL-37 on lupus mice in vivo . Objectives: This study aims to determine the inhibitory effect of IL-37 in lupus mice and lupus nephritis in vivo, and to expose the IL-37 related mechanisms of cell and molecules that inhibits the inflammmation in lupus nephritis. Methods: MRL-Fas lpr mice with mild and advanced disease were treated with lentiviral vector pLVX-IL-37b. The protein levels of IL-37b in serum and tissue, IL-17, IL-6, IL-10 and TGFβ-3 produced by cell culture from spleen and kidney of mice were measured by ELISA, the relative mRNA expression of these cytokines in PBMCs was detected by RT-PCR, and the frequency of Th17 and Treg cells in splenocyte were determined by FACS. Results: Our results show that IL-37 was highly effective in prolonging survival, alleviating the pathologic characteristics of lupus nephritis (LN) in MRL-Fas lpr mice by reducing the autoimmune complex deposition such as IgM, IgG and C3, decreasing the production of Inflammatory cytokines such as IL-17, IL-6 and promoting the anti-inflammatory cytokines IL-1 0and TGFβ-3. We also found that IL-37 protect lupus mice from LN associated with increasing the frequency of Treg cells and reducing the frequency of Th17 cells. Conclusions: These results indicate the protective action of IL-37 in LN, and strengthen the support for IL-37 as a new target for therapy of SLE. Disclosure of Interest: None declared